2008
DOI: 10.1021/es801865d
|View full text |Cite
|
Sign up to set email alerts
|

Total Nitrogen Content and δ15N Signatures in Moss Tissue: Indicative Value for Nitrogen Deposition Patterns and Source Allocation on a Nationwide Scale

Abstract: To evaluate a new N-monitoring program in the framework of the UN-ECE ICP-Vegetation program using mosses as bioindicators, 490 moss samples were collected at 220 sites in Austria and analyzed for total N (N content) and delta(15)N signatures. Within-site variability of N content and delta(15)N signatures was tested for the first time on a large scale and was extremely low compared to between-site variability. N content in moss tissue ranged between 0.76% and 1.99% and delta(15)N signatures between -10.04 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 33 publications
1
36
0
2
Order By: Relevance
“…This study reveals that mosses can potentially be used as biomonitors of total This study may be regarded as a cross validation of European moss data and EMEP model data for N, but is complicated by both potential limitations in the of mosses as monitors of atmospheric N deposition (Harmens et al, 2008b;Zechmeister et al, 2008) and the uncertainties in the modelled nitrogen deposition, including uncertainties in emissions (Lieven et al, 2009). The moss technique provides a tool for validating the spatial pattern for modelled EMEP air concentrations and depositions of nitrogen compounds at a higher spatial resolution than can be achieved using the EMEP measurement stations throughout Europe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study reveals that mosses can potentially be used as biomonitors of total This study may be regarded as a cross validation of European moss data and EMEP model data for N, but is complicated by both potential limitations in the of mosses as monitors of atmospheric N deposition (Harmens et al, 2008b;Zechmeister et al, 2008) and the uncertainties in the modelled nitrogen deposition, including uncertainties in emissions (Lieven et al, 2009). The moss technique provides a tool for validating the spatial pattern for modelled EMEP air concentrations and depositions of nitrogen compounds at a higher spatial resolution than can be achieved using the EMEP measurement stations throughout Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Carpet-forming ectohydric mosses might potentially be used as biomonitors of atmospheric N deposition as well (Pitcairn et al, 1995(Pitcairn et al, , 2006Poikolainen et al 2009;Salemaa et al, 2008;Solga et al, 2005;Zechmeister et al 2008). A pilot-study in Scandinavian countries showed a strong linear relationship between the total N concentration in mosses and EMEP-modelled atmospheric N deposition rates (Harmens et al, 2005).…”
mentioning
confidence: 99%
“…Across a gradient of nitrogen deposition in northeastern U.S., Pardo et al (2007aPardo et al ( , 2007b showed that foliar δ 15 N was strongly correlated with N deposition, and was also positively correlated with net nitrification potential and negatively correlated with soil C:N ratio. In this sense, plant foliar δ 15 N could be used as a useful indicator in reflecting the response of plants to anthropogenic N deposition in an area (Emmett et al, 1998;Garten and Hanson, 1990;Koopmans et al, 1997;Liu et al, 2007;Pardo et al, 2007a;Sah, 2005;Zechmeister et al, 2008). Meanwhile, it might be used to evaluate the effect of atmospheric N deposition and nitrogen saturation in forest ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, however, that the lowest sampling point was located on the territory of a city with a large population, that is, the region was enriched in nitrogen containing compounds. In Aus tria, the studies of d 15 N values in tissues of a few moss species, which were collected from 220 sampling points that were located pretty much evenly on the ter ritory of the country (2.5 sampling points per 1000 km 2 ), demonstrated the highly significant posi tive correlation between d 15 N values in moss tissues and the sampling point altitude [54]. To summarize, mosses, which, as well as lichens, belong to thallus containing and poikilohydric organisms, demonstrate a different dependence of d 15 N values on the habitat altitude compared to the X. camtschadalis vagrant lichen in the Khangai.…”
Section: Methodsmentioning
confidence: 99%